Thermal Equations for Predicting Foot Skin Temperatur - Pui-Ling Li; Kit-lun Yick; Joanne Yip; Sun-pui Ng (ACHSM, 2019)
Purpose: Studying the foot skin temperature of both the young and elderly is important for preventing foot diseases and improving thermal comfort and variability during gait. However, few studies have predicted the thermal conditions in footwear under different variables. The aim of this study is to therefore formulate thermal equations for both the young and elderly to predict their foot skin temperature under the variables of age, gender, activity level and various properties of different types of footwear. Methodology: A total of 80 participants between 20 and 85 years old are recruited in this study, including 40 younger subjects (mean: 23.0; SD: 4.05) and 40 elderly subjects (mean: 69.8; SD: 4.59). They are tasked to sit, walk and run in a conditioning chamber. Findings: Regression equations for predicting the foot skin temperature of the young and elderly people are formulated, with R squares of 0.513 and 0.350 respectively. The level of activity is the most important factor when predicting the foot skin temperature. The material properties of the footwear also show a significant impact on the foot skin temperature of the elderly. Value: The findings of this study provide the basis for better thermal comfort and help to facilitate the footwear design process.